The Effect of Slap the Board Game on Students’ English Vocabulary at SDN 3 Menteng Palangka Raya - Diana Febri Wuri Nastiti; Tampung N. Saman; Akhmad Fauzan; Debora Natalia Naibaho (English Education Journal, 2025)
This study aims to find the effect of ‘Slap the Board’ game on students' English vocabulary retention at SDN 3 Menteng Palangka Raya, Indonesia. This research used quantitative approach with pre-experiment research type and One-Group Pre-test-Post-test Design. The research was conducted in an elementary school with a total sampling of 16 third-grade students, consisting of 5 male students and 11 female students. The data were collected using a multiple-choice test instrument with 20 questions, given in the pre-test and post-test. The data were analyzed using inferential statistics through Shapiro-Wilk normality test and paired sample t-test. The results showed that students' English vocabulary mastery had an average of 57.5 in the pre-test, and after the implementation of the “Slap the Board” game, students' vocabulary retention increased with an average of 75 in the post-test. Statistical analysis showed that the “Slap the Board” game had a significant effect on students' English vocabulary mastery with a sig. (2-tailed) 0.001, which is smaller than the significance level α = 0.05. Thus, H₀ is rejected and H₁ is accepted. So, the “Slap the Board” game which involves kinesthetic activities and competition can improve the ability to retain English vocabulary and create a more fun and interactive learning atmosphere.